The agrarian social structure of Pehuajoïs party (2010) - Moreno, Manuela (Centro de Historia Argentina y Americana, 2011)
As a product of the ongoing transformations in the Agricultural sector in Argentina, recent debates in the social sciences have compared the new characteristics of development with older forms. Inside this field of debates, the question of the agrarian actors at present has been particularly relevant. Though their exists a great quantity of works that approach the problems of the actors, few analyses make reference to their productive roles. The present article presents a case study of Pehuajó's party. It provides a description of the social agrarian structure, focusing on the forms in which production develops as a result of the links between different actors, and establishing "rupture" points that caracterize the older forms of development.